Holding Us Accountable: Arts Education in California Multiple Subject Credential Programs. (2nd January 2019) - Lorimer, Maureen Reilly
Abstract : To ensure a robust and comprehensive educational experience, every K-12 learner must have access to high quality Visual and Performing Arts (VAPA) education. To make this happen, their teachers must be effectively prepared to provide excellent art education experiences. Although arts education is required in many states (including California) as part of licensure requirements, little is known about the actual implementation of these policies. To better understand this preparation gap, a three-part statewide study analyzed the status of arts education in California teacher preparation programs. Findings from survey, interview, and document analysis indicate that arts education experiences increase candidate confidence and deepen their understanding of the benefits associated with using the arts to meet the needs of diverse learners. However, inconsistent program requirements among institutions of higher education contribute to a lack of cohesion in art preparation throughout the state.